The territorial and strategic context of Stamford, Lincolnshire, in the early tenth century. (October 2017) - Haslam, Jeremy
Abstract: A new view is put forward concerning the course of the early development of Stamford in southern Lincolnshire in its wider geopolitical context, through an analysis of its topography, archaeology and early history. It is concluded that a Mercian royal centre on the site of St Peter's church and the later castle was refortified by the Scandinavian forces in the late ninth or early tenth century, and that it was this stronghold which was taken over by the forces of King Edward the Elder in c . 918. The king thereupon built two burhs – defended quasi-urban settlements – on the two sides of the river Welland. These were linked by a bridge, forming a single strategic unit, on the West Saxon model. Each of these burhs was assigned a burghal territory, the inhabitants of which owed a range of services to the king at the burh. This process can be seen as the origin of what has been called the 'Danish burh' on the north bank. These burhs, with their associated territories, became the instruments for a new level of control of the area by Edward and subsequent West Saxon kings. This reassessment enables a new model to be articulated concerning the temporal and functional development of burhs and their associated cadastral units - shires, burghal territories, wapentakes, hundreds and town fields - in the context of the political changes involved in the early tenth-century conquest and reabsorption of the Viking-held territories in the eastern Midlands by the West Saxon king. Highlights: Reassesses the prevailing idea that Stamford north of the River Welland developed as a Danish stronghold. Uses topographical and other evidence to argue its origins as a single burh-bridge-burh unit created by the king in 918. Reconstructs the new burghal territories around Stamford to demonstrate how they gave the king control on a regional basis. Examines the wider geopolitical context of burhs, hundreds and shires in the northeast Midlands in the tenth century.